2022
DOI: 10.3390/children9050655
|View full text |Cite
|
Sign up to set email alerts
|

Congenital CMV, Lights and Shadows on Its Management: The Experience of a Reference Center in Northern Italy

Abstract: Congenital cytomegalovirus infection (cCMV) is the most common congenital viral infection, with a consistent rate of morbidity, mortality, and long-term sequelae, especially in the case of late diagnosis. Nevertheless, a universal screening for CMV is not currently recommended, and global awareness about this infection, as well as accurate and shared indications on follow-up and treatment, are still lacking. We reviewed data about 59 suspect cCMV cases who referred to our center from 2014 to 2021. We report 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Among adults genital secretions are a common fluid for CMV shedding, consistent with several studies that identified sexual risk factors for CMV seropositivity or seroconversion (10,13,19). Another important transmission route for primary infection consists in solid organ transplantation (SOT), especially in cases where there is a serological mismatch between donor and recipient (the recipient is CMV seronegative and the donor is seropositive) (20).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Among adults genital secretions are a common fluid for CMV shedding, consistent with several studies that identified sexual risk factors for CMV seropositivity or seroconversion (10,13,19). Another important transmission route for primary infection consists in solid organ transplantation (SOT), especially in cases where there is a serological mismatch between donor and recipient (the recipient is CMV seronegative and the donor is seropositive) (20).…”
supporting
confidence: 59%
“…The heterogeneous CMV seroprevalence appear to be related with race, ethnicity, socioeconomic status and education level (11). Focusing on Italy, the seroprevalence of HCMV appear to be as high as 70-80% (12,13).…”
mentioning
confidence: 96%
“…Therefore, according to the general agreement, CMV serologic testing should be offered only to pregnant women with symptoms and/or signs suggestive of primary CMV infection (e.g., influenza-like illness and/or fetal abnormalities on prenatal ultrasound examination) [ 42 ]. However, most pregnant women want to have CMV serological screening once informed about cCMV infection [ 43 ]; some of them make use of the maternal serological screening even if it is not recommended by the national guidelines [ 28 , 30 , 38 , 44 , 45 ]. As a matter of fact, maternal CMV screening followed by targeted neonatal CMV screening (testing neonates whose mothers become seropositive during pregnancy) may help identify asymptomatic cCMV cases in an early stage; Naessens et al reported that this type of screening allowed the detection of 82% of all cCMV infections [ 46 ].…”
Section: Current Controversies In Preventive Diagnostic and Therapeut...mentioning
confidence: 99%
“…Human Cytomegalovirus (HCMV) is a ubiquitous herpesvirus that is highly widespread throughout the world with a seroprevalence rate among women of reproductive age ranging from 100% in Africa and Asia to 45.6%–95.7% in Europe and North America ( 1 ). Focusing on Italy, HCMV seroprevalence appears to reach 70%–80% ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…As congenital HCMV infection, primary and non-primary maternal infection (exogenous reinfection with a different strain or endogenous viral reactivation) of the virus during pregnancy can result in in utero transmission to the developing fetus (vertical route) ( 4 , 5 ). In the postnatal period, HCMV is transmitted through exposure to different biological fluids (saliva, stool, and urine) as a consequence of community exposure or by genital secretions, especially in the adult stage ( 1 , 3 , 6 , 7 ). Another important route of transmission of primary infection is solid organ transplantation, especially in cases where there is a serological mismatch between donor and recipient (HCMV-seronegative recipient/HCMV-seropositive donor) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%